2009
DOI: 10.1111/j.1742-4658.2009.07451.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic resistance to articular chondrocyte apoptosis – a possible mechanism of maintaining homeostasis of normal articular cartilage

Abstract: Hypoxia and hypoxia-related genes are important factors in articular chondrocytes during cartilage homeostasis and osteoarthritis. We have investigated the various apoptotic factors that show significance in synovial fluid obtained from normal and experimental osteoarthritic animal models and have evaluated the effect of hypoxia on articular chondrocyte apoptosis induced by these apoptotic factors. Mature beagle dogs underwent surgical transections of ligaments and medial meniscectomies to explore the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…The antiapoptotic tumor gene survivin has been extensively studied in cell cycle and apoptosis assays in tumor cells, with little available data in primary cells and chondrocyte biology so far [30]. Previous studies stressed the "oncofetal" pattern of survivin gene expression and its absence in adult differentiated cells and tissues [9]. In recent publications, a role for survivin in RA has been discussed and convincing data about its importance for the progression of this inflammatory disease have been presented [18,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiapoptotic tumor gene survivin has been extensively studied in cell cycle and apoptosis assays in tumor cells, with little available data in primary cells and chondrocyte biology so far [30]. Previous studies stressed the "oncofetal" pattern of survivin gene expression and its absence in adult differentiated cells and tissues [9]. In recent publications, a role for survivin in RA has been discussed and convincing data about its importance for the progression of this inflammatory disease have been presented [18,24].…”
Section: Discussionmentioning
confidence: 99%
“…In osteoarthritis, the influence of proapoptotic mechanical and metabolic factors increases and is antagonized by the initiation of various molecular antiapoptotic mechanisms [6-8]. The initiation of the various protective molecular mechanisms have been discussed in previous studies [9-11]. …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that mitochondria participates in the process of anti-apoptosis and necrosis in different ways and the MMP can reflect the function of mitochondria (Seol et al 2009;Wang et al 2009a, b). It is reported that recovery of MMP can protect against injuries such as diabetes, hypoxia, and ischemia (Iijima 2006;Manna et al 2009;Seol et al 2009). Interestingly, we found that hypoxia for 24 h declined MMP and 200 μg/ml of 5-HMF rescued the decline of MMP partly.…”
Section: Discussionmentioning
confidence: 99%
“…There is now increasing evidence that ERK has the dual effects in hypoxia and compounds that influence ERK can function as protective agents (Montagut and Settleman 2009;Muslin 2008;Ohori 2008). Furthermore, mitochondria participate in the process of hypoxic response in different ways and the mitochondrial membrane potential (MMP) can reflect the function of mitochondria (Seol et al 2009;Wang et al 2009a, b;Snyder and Chandel 2009). It is reported that recovery of MMP can protect against ROS-mediated injuries such as hypoxia and ischemia (Iijima 2006;Zhou et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Низкая концентрация кислорода является оптимальной и протективной для суставного хряща, поскольку при гипоксии наблюдалось ингибирование каспазы 8 и продукции ROS, которые были предварительно индуцированы в суставных хондроцитах обработкой ингибитором протеосом и стимулятором апоптоза ФНО-зависимым ингибирующим апоптоз лигандом (TNF-related apoptosis-inducing ligand; TRAIL) в условиях нормальной (20%) концентрации кислорода [72]. В присутствии оптимальной (5%) концентрации кислорода для суставных хондроцитов свиньи наблюдались продукция максимального количества АТФ и наиболее эффективная защита от стимулирующего воздействия ИЛ1 и NO, тогда как в присутствии 20% или 1% концентрации кислорода уровни АТФ снижались, а экспрессия АМРК повышалась [73,74].…”
Section: функции позитивных регуляторов Mtor в хондроцитахunclassified